Pengaruh Kenyamanan, Kualitas Pelayanan, Dan Keragaman Produk Terhadap Kepuasan Pelanggan Pada PT. Indometro Surya Andola Kota Metro - Choirunisa, Melinda Putri; Suryadi, Suryadi (Jurnal Manajemen DIVERSIFIKASI, 2023)
The purpose of this study was to determine the effect of comfort, service quality, and product diversity and customer satisfaction of PT. Indometro Surya Andola Metro City. The method used in this research is the explanatory survey method. This type of research is quantitative research with the object of research is convenience, service quality, and product diversity and customer satisfaction. The research population is the customers of PT. Indometro Surya Andola Metro City with the number of samples taken as many as 96 respondents. Data collection techniques using questionnaires. The analytical tool used is data quality analysis and multiple linear regression analysis. The results showed that comfort, service quality, and product diversity both partially and simultaneously had a positive and significant effect on customer satisfaction, so it is recommended for companies to improve comfort, service quality and product diversity considering that these have a significant influence on customer satisfaction.